Mechanisms and management of self-resolving lumbar disc herniation: bridging molecular pathways to non-surgical clinical success - Yan Zhao; Zhiwei Jia; Abudunaibi Aili; Aikeremujiang Muheremu (Journal of Orthopaedic Surgery and Research)
Abstract Spontaneous resorption of lumbar disk herniation (LDH) presents a promising avenue for the non-surgical management of herniated disks. Here we present a 40-year-old female with severe L5/S1 herniation who experienced spontaneous resorption confirmed by MRI. The patient adhered to a comprehensive non-operative treatment regimen comprising NSAIDs, heat therapy, massage therapy, acupuncture, and kinesitherapy. Over two years, the patient showed substantial clinical improvement, with significant pain reduction and MRI evidence of disk resorption, resulting in a marked decrease in their visual analog scale (VAS) pain scores. Through a systematic review of existing literature, we identify that spontaneous resorption is associated with mechanisms such as inflammation, neovascularization, macrophage infiltration, matrix degradation, disruption of immune privilege, apoptosis and autophagy, and disc dehydration. Clinical predictors for spontaneous resorption of LDH include the size, type and composition of the herniation, rim enhancement on contrast-enhanced MRI, and involvement of the posterior longitudinal ligament (PLL). Future research should focus on elucidating the molecular mechanisms of resorption, regulation of inflammatory response, macrophage polarization, matrix degradation, immune privilege and neovascularization, developing advanced imaging techniques to predict resorption potential, and exploring personalized treatment strategies based on machine learning and deep learning prediction models.